(3cJGH GdYdds - (3eMeO Hf YjSi Hf ShQI Hf ehSi GdSdej GdHhZj GdJQePj, CHh YjSi ,J (B279 (3g` s
(3ChdgG (B:s
(3hHGdESfGO CNHQfG GdbGVi CHh YGeQ GdCROi CHh YjSi GdMGaX GdJQePi bGd LejY eG ai gPG GdcJGH ef GdMOjK gh eYehd Hg hHg CNP HYV Cgd GdYde s
(3BNQgG (B:s
(3bGd CHh YjSi gPG MOjK ZQjH ef gPG GdhLg dGJYQag ef MOjK CfS Hf eGdc EdG ef gPG GdhLg hbO Qhi Yf YeQh Hf CejI GdVejQi Yf GdfHi Udi Gddg Ydjg hSde fMh gPG hbO hVYfG gPG GdcJGH Ydi GdGNJUGQ deG QLhfG ajg ef GdefaYI BNQ cJGH GdYdd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YhQV HCUdjf UMjMjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1440s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs